2020
DOI: 10.3390/ijerph17239052
|View full text |Cite
|
Sign up to set email alerts
|

Cyberincivility Experience of Korean Clinical Nurses in the Workplace: A Qualitative Content Analysis

Abstract: Although clinical nurses use online platforms to acquire health-related information and communicate with other healthcare providers, there are increasing reports on their incivility exposure in cyberspace. However, an in-depth understanding of their cyberincivility experience is lacking. This study aimed to identify Korean clinical nurses’ perception and experience of cyberincivility. A qualitative study was conducted. Twenty clinical nurses from seven private and public hospitals in the Seoul metropolitan are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In a study by Kitsis et al [ 30 ], medical students and faculty perceived social media content as unprofessional if it contained derogatory remarks toward certain patient groups (ie, Medicaid patients) or negative comments about work stress, colleagues, and patients. Similarly, Kim et al [ 40 ] studied Korean clinical nurses’ experiences of cyberincivility, including a lack of respect and morality within health professions. They suggested that interprofessional or intraprofessional aggression in online spaces could occur when health care professionals lacked an understanding of the roles of workers in other occupations or when users were tired from work and lost control of their emotions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Kitsis et al [ 30 ], medical students and faculty perceived social media content as unprofessional if it contained derogatory remarks toward certain patient groups (ie, Medicaid patients) or negative comments about work stress, colleagues, and patients. Similarly, Kim et al [ 40 ] studied Korean clinical nurses’ experiences of cyberincivility, including a lack of respect and morality within health professions. They suggested that interprofessional or intraprofessional aggression in online spaces could occur when health care professionals lacked an understanding of the roles of workers in other occupations or when users were tired from work and lost control of their emotions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kim et al [ 40 ] studied Korean clinical nurses’ experiences of cyberincivility, including a lack of respect and morality within health professions. They suggested that interprofessional or intraprofessional aggression in online spaces could occur when health care professionals lacked an understanding of the roles of workers in other occupations or when users were tired from work and lost control of their emotions [ 40 ]. Researchers have also highlighted that experiences of interprofessional or intraprofessional aggression in cyberspace can increase the workload and stress of health professionals by generating mistrust and reducing teamwork [ 30 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation